Źródła dostaw warzyw i owoców na rynki miast Dolnego Śląska - Nowak, Marek; Szybiga, Krystyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper presents fruit and vegetables production and consumption on the Lower Silesia selected towns territory. There was established the balance degree of market analyzed in the paper and the deficit level of products. Moreover, the deliveries of shops, gastronomy, and canteen of public institutions for fruit and vegetables structure were defined. There was observed the biggest share of the delivery wholesale market "Targpiast" in Wrocław. It was also confirmed that the Lower Silesia region was self-sufficient in the range of the distribution and deficient in the range of fruit and vegetables production. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 322-328